A Study of Imperial Maids’ Life Through Tang’s Poetry - Lin, Xuc (Bina Nusantara University, 2012)
Article observed the life of Tang’s imperial maids through the poetry of Tang Dynasty. . Imperial maids were started from Sui Dynasty, especially Emperor Sui Yangdi’s period, and Tang’s imperial maids were many. Emperor with various kind of reasons, in most every year would choose some girls and took them into his palace and they worked as imperial maids. They were girls from ordinary people, respectable, and noble families. Those girls who once entered imperial palace, theyb would be very hard to come out. They had to obey the regulation in the palace. Through some poetry it could be portrayed the imperial maids’ lifetime in serving the emperor，imperial concubines and got rest after midnight. Except for working, they weren’t able to come out from palace, they couldn’t go home to visit their family, even got married, their lives were full of loneliness. If they were sick, or old, the emperor wouldn’t like them anymore, they would be sent away anytime. Even if they left imperial palace, and got their freedom, but most of them lived tragically.